High speed green-taxiing motor-generator drive system for mild hybridization of turboprop aircraft - Chen, Yuzheng (2023)
The More-Electric Aircraft (MEA) has been identified as a major future aircraft due to the urgent requirement to reduce CO2 in the aviation area. Meanwhile, as a commonly used thrust power source in commuter aircraft, turboprop engines can be made more fuel-efficient by the addition of a mechatronic device into their gearbox. In the University of Nottingham, an integrated Motor-Generator (M-G) drive system functioning as this mechatronic device has been developed for the next-generation turboprop. This M-G system provides auxiliary thrust to accelerate the turbo engine start-up on the ground, using electrical power from batteries. The same system is used as a generation system when the aircraft is in the air and supplies electrical power to on-board electrical loads. This PhD project is focused on the development of this M-G system and is thoroughly described in the thesis, including the machine design, power electronic converters and their control development. Due to redundancy considerations, a dual three-phase machine was developed to ensure uninterrupted power delivery, even if a fault should occur. The corresponding power converter was designed using SiC power modules to achieve high power density. The entire system, including the machine, six-phase converter, and controller, has a customized cooling system, designed to be integrated into the engine gearbox. The control algorithm was one of the most challenging parts of the M-G system due to the absence of a position sensor and is the main contribution of this PhD research. An I-F open-loop and Model Reference Adaptive System (MRAS) sensorless combined solution was proposed to cover the entire speed range. The stability issue of MRAS for high-speed drives needs to be considered carefully due to a low modulation frequency (of the power electronic converter) to the electrical machine fundamental frequency ratio (M-F ratio). The entire M-G drive system has been modelled in the z-domain with particular efforts on modelling this non-linear system; in particular, the estimated rotor angle was used in the frame transformations (e.g., ABC to DQ frame). With the discrete z-domain model, eigenvalues of the system model have thus been used to analyse the system stabilities. The PI controller for this high-speed M-G system can thus be designed with confidence that the system will be stable with selected parameters. The developed sensorless control scheme has been validated on the M-G system at full speed, and full power range using testing facilities within the University of Nottingham